2023
DOI: 10.3390/languages8030194
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Effects of Pedagogical Translanguaging in EFL Classrooms: A Systematic Review

Abstract: In response to calls for more research to assess the effects of translanguaging on substantive learning outcomes, this systematic review begins that process by synthesising existing research on pedagogical translanguaging approaches that have been formally assessed for effectiveness in English as a Foreign Language (EFL) classrooms. A systematic process of searching and selecting the literature found 10 eligible studies. Data were extracted for narrative synthesis and quality appraisal. Results showed that ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The standard of evidence looked for must be at least as strong as reviewers would accept for established 'facts' in real life. The sieve has now been used widely and formally by research teams to assist in their reviews of evidence since 2014(e.g., El Soufi & See, 2019Fan & See, 2022;Huang & Chalmers, 2023;Neelen & Kirschner, 2020;Owen et al, 2022;See et al, 2022;Siddiqui & Ventista, 2018), as well as by countless PhD students in their theses. It has been explained in videos for specific areas like evidence on second language learning (Chalmers, 2016), and discussed widely on social media in fields beyond education and social science (e.g., https:// twitt er.…”
Section: Discussionmentioning
confidence: 99%
“…The standard of evidence looked for must be at least as strong as reviewers would accept for established 'facts' in real life. The sieve has now been used widely and formally by research teams to assist in their reviews of evidence since 2014(e.g., El Soufi & See, 2019Fan & See, 2022;Huang & Chalmers, 2023;Neelen & Kirschner, 2020;Owen et al, 2022;See et al, 2022;Siddiqui & Ventista, 2018), as well as by countless PhD students in their theses. It has been explained in videos for specific areas like evidence on second language learning (Chalmers, 2016), and discussed widely on social media in fields beyond education and social science (e.g., https:// twitt er.…”
Section: Discussionmentioning
confidence: 99%
“…This failure to take appropriate steps to minimise bias in healthcare research, where these design considerations are generally well-understood, is concerning. In applied linguistics research, it is still all too common to find research that has not taken appropriate steps to minimise the potential for biases to mislead (see, for example, the risk of bias appraisals in Chalmers, 2019;Huang & Chalmers, 2023). Of course, researchers working within any research paradigm should do what they can to ensure that their work is rigorous and fair.…”
Section: Poorly or Inappropriately Designed Researchmentioning
confidence: 99%
“…Studies that have been carried out by contemporary academics have shown that translanguaging has the inherent capability to harness the linguistic talents of pupils effectively and successfully. Despite the statements that have been made about the influence of translanguaging on the academic and pedagogical results of students, the actual implementation of this concept is often disregarded by practitioners (Creese & Blackledge, 2010; Danping, 2019; García & Wei, 2014; Huang & Chalmers, 2023).According to Johnson and Martinez (2020), the term "translanguaging" refers to a communication technique that involves the intentional and systematic use of a person's multilingual talents with communication. García and Wei (2014) emphasize that it enables the smooth representation of concepts across many language systems, adding to the benefits of this technology.…”
Section: Introductionmentioning
confidence: 99%